FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT XYZ CIKARANG - IQBAL, MUHAMMAAD; RUSWIDIONO, WASISTO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to determine whether there is influence of leadership style, motivation and work discipline on employee performance at PT XYZ Cikarang. This research was conducted to determine the decline in the annual production rate at the company. This research was conducted at PT XYZ Cikarang, by taking 82 employees as research samples using purposive sampling technique. Collecting data using observation methods and questionnaires. The data analysis technique used is multiple regression analysis. Based on the study conduct, the results of the analysis showed that leadership style and work discipline have effect on employee performance.